Neznan rokopis Jurija Japlja o slovenskem jeziku iz leta 1773 - Duličenko, Aleksandr Dmitrievič (Slavistična revija, 2004)
Japelj wrote about Slovene in 1773 as part of the plan by H. L. Ch. Bachmeister to compare "all languages". The author of this article found the manuscript in 1995 in the manuscript secion of the Russian National Library in St. Petersburg. The article includes linguistic and textological analysis of the text, which is also published in its entirely at the end of the article.
Keywords: 18.st.; history; Japelj, Jurij, 1744-1807; rokopisi; Slovene; slovenščina; transkripcija; zgodovina